Rousseau, Bodin, and the Medieval Corporatist Origins of Popular Sovereignty. (February 2022) - Edelstein, Dan
This essay reconsiders Jean-Jacques Rousseau's debt to Jean Bodin, on the basis of Daniel Lee's recent revision of Bodin as a theorist of popular sovereignty. It argues that Rousseau took a key feature of his own theory of democratic sovereignty from Bodin—namely, the dual identity of political members as both citizens and subjects of the state. It further makes the case that this dual identity originates in medieval corporatist law, which Bodin was summarizing. Finally, it demonstrates the lasting impact of corporatist law in eighteenth-century France, highlighting Rousseau's direct borrowings from the corporatist language and logic of contemporary commercial societies. In this regard, the article revisits and updates Otto von Gierke's classic argument about the origins of the state in corporatist thought.